Salacia tortuosa Griff. (Celastraceae) - an Extended Distribution from Andaman Islands, India - Lakshminarasimhan, P.; Ray, L. N. (Indian Forester, 1994)
Salacia tortuosa Griff. Is reported here as aD addition to the Indian flora from Andaman Islands.